Transgenerational epigenetic inheritance: how important is it? - Grossniklaus, Ueli (2013)
Much attention has been given to the idea of transgenerational epigenetic inheritance, but fundamental questions remain regarding how much takes place and the impact that this might have on organisms. We asked five leading researchers in this area — working on a range of model organisms and in human disease — for their views on these topics. Their responses highlight the mixture of excitement and caution that surrounds transgenerational epigenetic inheritance and the wide gulf between species in terms of our knowledge of the mechanisms that may be involved.